Korelasi Larangan Kekerasan Dalam Rumah Tangga Menurut Pasal 5 Undang-Undang Nomor 23 Tahun 2003 tentang Penghapusan Kekerasan Dalam Rumah Tangga dengan Konsep Nusyuz dalam Hukum Islam - Sarip Hidayat (Uniku Law Review, 2024)
The state must protect its citizens from acts of violence in the household. This aims to eliminate all acts of violence that occur in the household, with the issuance of Law Number 23 of 2004 which is a real form of government in eliminating acts of violence and efforts to protect society. This study uses normative juridical, using a descriptive analysis approach. In Islamic law, Nusyuz is a way to educate a husband towards his wife so that the rights and obligations of the household are fulfilled, in Law Number 23 of 2004 Article 5 states that acts of violence are: physical, psychological, sexual violence and neglect in the household. While the concept of Nusyuz in Islam, when a wife commits an act of Nusyuz, the husband has the right to beat her, separate her from the bed and advise her. This is highly correlated with Article 5 of the Law, namely for the settlement of domestic violence, namely through penal mediation by seeking to use a win-win solution and trying to be a solution to problems in the criminal justice system.